A larger low‐flow‐mediated constrictor response is associated with augmented flow‐mediated dilation in the popliteal artery. (29th August 2021) - O'Brien, Myles W.; Petterson, Jennifer L.; Johns, Jarrett A.; Mekary, Said; Kimmerly, Derek S.
Abstract: In the brachial artery, conflicting evidence exists regarding the relationship between the low‐flow–mediated constriction (L‐FMC) and subsequent flow‐mediated dilation (FMD) responses, which may confound interpretation of the latter. The popliteal artery is a common site for atherosclerotic development, which is preceded by endothelial dysfunction. We aimed to determine whether the magnitude of popliteal L‐FMC impacted FMD responses, which is currently unknown. L‐FMC and FMD were assessed in the popliteal artery via high‐resolution duplex ultrasonography and quantified as the percent change in diameter (from baseline) during ischaemia and in response to hyperaemia, respectively. Using partial correlations and multiple regression analyses, we evaluated the association between popliteal L‐FMC on FMD in 110 healthy participants (60 females; 42 ± 22 [19–77] years). All variables univariately associated ( p < 0.05) with popliteal relative FMD (relative L‐FMC, log‐SRAUC, age, systolic blood pressure, diastolic blood pressure, resting shear rate) were inputted into a model that explained 35% of the variance. The reactive hyperaemia stimulus (log‐SRAUC : β = 1.10) and relative L‐FMC ( β = −0.39) were the only independent predictors of FMD (both, p < 0.01). Relative L‐FMC was negatively correlated to relative FMD, after controlling for the significant univariate predictor variables listed above ( R = −0.30; p = 0.002). An augmented (ie healthier) L‐FMC response was linked with a larger FMD response as determined by the independent inverse association observed between these shear‐stress–mediated measures of vasoreactivity.